A Stage-wise Optimal PMU Allocation using BCSA for Improving the Sensitive Bus Observability - Maji, Tapas Kumar; Acharjee, Parimal (Procedia computer science, 2018)
Despite of substantial development in measurement technology of phasor measurement units (PMUs), the utilization of PMU is still barely appreciated by the power industries due to its high installation cost. It motivated the researchers to find an optimal set of locations to obtain full observability of a network with least number of PMUs. A stage-wise optimal PMU allocation (SWOPA) approach is proposed in this paper using binary crow search algorithm (BCSA) based on the measurement reliability assessment of some sensitive buses. The effectiveness of the multiple outcomes (MOCs) obtained while solving the OPA problem is analyzed and a sensitive bus observability (SBO) assessment, associated with generator, weaker, and transformer-connected buses is mathematically modeled in this regards to determine the best outcome from those MOCs. The observability criteria of such sensitive buses are also incorporated in order to provide ranking in PMU bus nomination at each stage. The proposed method is demonstrated on IEEE 57-bus test system and its performance is verified with other methods.